EFFECTS OF WASHING DIRTY EGGS OF GEESE WITH BORIC ACID AND VINEGAR ON HATCHABILITY AND MICROBIAL LOADS - Mehmet EROGLU; Zeki ERISIR; Ulku Gulcihan SIMSEK; Seda Iflazoglu MUTLU; Yasin BAYKALIR; Alper GUNGOREN; Muhsin MUTLU; Gizem ADIYAMAN KARAKUS; Selçukhan AKARSU (Journal of Animal and Plant Sciences, 2025)
This study aimed to evaluate whether washing dirty goose eggs with tap water, vinegar, and boric acid solutions could improve hatching performance and reduce microbial load. A total of 3,360 eggs were used for hatching performance assessments, while 84 eggs were analyzed for microbiological parameters. The study consisted of seven treatment groups: physically clean eggs (PC), unwashed dirty eggs (NC), eggs washed in tap water (TW), eggs washed with a vinegar solution containing 2% acetic acid (S2), eggs washed with a vinegar solution containing 4% acetic acid (S4), eggs washed with a 2% boric acid solution (B2), and eggs washed with a 4% boric acid solution (B4). Hatchability of set eggs and hatch of fertile eggs improved significantly in the PC, S2, and B2 groups (P<0.01). Embryonic mortality was significantly low in the PC and B2 groups (P<0.05). Significant differences were observed between the groups for total mesophilic aerobic bacteria (TMAB) (P<0.001), total coliforms (TCN) (P<0.01), and Escherichia coli (P<0.01). The lowest TMAB counts were recorded in the S2 and B4 groups, while the lowest TCN counts were observed in the B4 group. Bacterial analysis of egg contents showed that all bacterial groups were below detectable limits. In conclusion, washing dirty goose eggs with tap water, vinegar, or boric acid solutions (2% and 4%) effectively reduced the microbial load on the eggshell for all examined microorganisms and significantly improved hatching parameters compared to dirty eggs.
Keywords: Egg; Microbial Load; Vinegar; Boric Acid; Washing